(untitled) (International relations and international law Journal, 2016)
There are in this article safety problems in the region of the Southern Asia and India are considered. Position of India as natural leader among the states of the southern Asian subcontinent on a number of geographical, demographic and economic indicators , is fixed by is active regional policy. The position of India in questions of ensuring political stability in the Southern Asia has basic value for all complex of regional security. Increase of geopolitical and economic value of the Southern Asia in system of the modern international relations, on the one hand, and close interrelation between interests of regional security of the Southern Asia and national interests of India, with another, define relevance of this article which subject is the policy of India in the sphere of ensuring national and regional security.